Development of long bones of human extremities in fetal period - Młodziejowski, Bronisław (Anthropological Review, 1975)
The author has examined 235 human fetuses (123 males and 112 females) in the age from 4 to 10 lunar months. Following long bones of extremities were dissected: femur, tibia, fibula, humerus radius and ulna, moreover the author examined scapula and clavicle. Measurements taken on the bones considered also their unossified parts. Arithmetic means and other statistical characteristics of measurements are tabulated with respect to age of fetuses.